Motivation measurement of science student towards grouping e-learning - Abang Abai, Dayang Shobihah; Hamli, Hadi (Journal of Education and Learning (EduLearn), 2025)
During the two-year COVID-19 pandemic, lecturers must train themselves with information technology, assessment, and teaching expertise in order to move from face-to-face learning to virtual online learning. As a result, the current study aims to investigate the effect of student motivation on grouping e-learning in the ethics and civilization course. A total of 88 students from agriculture, fishing, and forestry were chosen to participate in the experiment. Students participated in online synchronous lectures for seven weeks and another seven weeks in online group presentations. After 14 weeks, students were given the attention, relevance, confidence, and satisfaction (ARCS) motivation model questionnaire to assess their motivation on the course. As a result, the ARCS questionnaire score was 4.62, indicating that student learning motivation was adequate. Furthermore, forestry students outperformed agricultural and fishery students in terms of ARCS model score. Male students who participated in the online grouping presentation had the greatest ARCS model score compared to female students. As a result, using an online group presentation learning system for asynchronous learning is possible and beneficial, particularly for male learners.